Consumer Decision-Making Process dan Perbandingan Brand Image Produk Parfum Menengah di Pasar Indonesia - Amadea, Resyla; Roswinanto, Widyarso (Journal of Management and Business Review, 2025)
Perfume is a product derived from the extraction of aromatic ingredients combined with alcohol and pure oil. The growing perfume industry, an increasing number of local perfume brands have emerged, using the term “Eau de Parfum” and offering products at affordable prices. This type of perfume is categorized as mid-range. This study was conducted by collecting and analyzing data inductively. Primary data were obtained through questionnaires distributed to 106 respondents, all perfume consumers. The survey included questions regarding various aspects of perfume usage, such as reasons for use, frequency of application, product information, advertisements, purchasing locations, and preferred perfume characteristics. The study focuses on four mid-range perfume brands currently being marketed extensively. These brands primarily utilize digital marketing strategies through social media platforms. By examining the diverse forms of digital content produced, this research also explores the brand image created through social media promotions and its influence on consumer purchase intentions. The findings indicate that brand image directly impacts consumers' willingness to purchase perfumes. As a sensory product, perfume is something consumers need to experience firsthand. Rather than price alone, consumers tend to prioritize the quality and longevity of the fragrance rather than price alone.